Masseter muscle thickness in relation to facial form in angle's normal occlusion and malocclusions: An observational study - Jasbir Meher; Salman Hasan Khan; Abhishek; Kanheyalal Sarada Prasad; Chitrang Dixit; Rajeev Kumar Singh (Wolters Kluwer Medknow Publications, 2024)
Background: Various clinical studies performed in adults have shown the relationship between craniofacial morphology and masticatory muscle function. However, the growth of the masticatory muscle has not received such attention, when compared with the volume of studies on the skeletal growth of face. With this background and considering the widespread use of ultrasonography (USG), the following study was undertaken to provide some insights into the relationship between muscle and bone and facial morphology. Methods: This was a prospective, observational study conducted over a period of three years from 2012 to 2015 to assess the correlation between the thickness of the masseter muscle in Angle's normal occlusion and the various malocclusions of the dental arch as well as the facial form. Patients with a full complement set of teeth, normal tooth morphology, Angle's normal occlusion, Angle's class I-III malocclusion, those with a history of third molar extraction, and impaction were included in the study. Those with a history of any prior orthodontic treatment, restorations, or any missing teeth (except the third molar) were exempted from the study. The greater thickness of masseter muscle in relaxed and clenched state was recorded on USG. Facial morphology was determined with the aid of facial photographs. Results: The study was conducted on 140 patients. The class I normal occlusion group had the thickest masseter muscle, while the class III malocclusion group had the thinnest masseter muscle. Facial parameters showed highly significant gender-wise differences in class I normal occlusion, class I malocclusion, and class II division II malocclusion. There was a significant negative co-relation between the thickness of masseter muscle and facial forms in all the categories of Angle's classification as indicated by a negative regression coefficient B (P < 0.05). Conclusion: The masseter muscle thickness correlated directly with male gender and normal occlusion, and inversely with the degree of malocclusion and facial form.